2000
DOI: 10.1152/ajpregu.2000.279.4.r1230
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic contribution to rat bladder hyperactivity after middle cerebral artery occlusion

Abstract: To evaluate the influences of gamma-aminobutyric acid (GABA) mechanisms on bladder hyperactivity after left middle cerebral artery occlusion, cystometric recordings were obtained from unanesthetized female rats. Intracerebroventricular administration of both muscimol (GABA(A) receptor agonist; 0.1-10 nmol) and baclofen (GABA(B) receptor agonist; 0.1-3 nmol) produced dose-dependent inhibitions of micturition with increases in bladder capacity (BC). The effects of high doses (1-10 nmol) were similar in sham-oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 24 publications
0
24
0
1
Order By: Relevance
“…Various cortical lesions are thought to lead to these symptoms due to damage to the cerebral inhibitory centers leading to uninhibited detrusor contractions [26]. Other cerebral infarction-induced factors that may lead to OAB include alterations in N-methyl-D-aspartic acid glutamatergic mechanisms [27], dopamine D2 receptor excitatory mechanisms [28], dopaminergic-glutamatergic interactions in the brain [29], a central mechanism sensitive to nitric oxide [30], and a decreased GAGA-mediated inhibition of micturition [31]. Other neurological entities that are known to cause OAB syndrome include Parkinson's disease, multiple sclerosis, and spinal cord injuries.…”
Section: Neurologic Factors Of Oabmentioning
confidence: 99%
“…Various cortical lesions are thought to lead to these symptoms due to damage to the cerebral inhibitory centers leading to uninhibited detrusor contractions [26]. Other cerebral infarction-induced factors that may lead to OAB include alterations in N-methyl-D-aspartic acid glutamatergic mechanisms [27], dopamine D2 receptor excitatory mechanisms [28], dopaminergic-glutamatergic interactions in the brain [29], a central mechanism sensitive to nitric oxide [30], and a decreased GAGA-mediated inhibition of micturition [31]. Other neurological entities that are known to cause OAB syndrome include Parkinson's disease, multiple sclerosis, and spinal cord injuries.…”
Section: Neurologic Factors Of Oabmentioning
confidence: 99%
“…These proteins and receptors may be involved in the regulation of nociceptive processing. Indeed, systemic or central administration of nociceptin, 28 enkephalins (intrathecal naloxone, 29 ), and GABA, 30 inhibits the micturition reflex. Interestingly, peripheral inflammation induces nociceptin in primary sensory neurons 31 and increases pro-dynorphin mRNA in dorsal horn neurons.…”
Section: Genes Involved In Bladder Physiologymentioning
confidence: 99%
“…Blok et al 18 demonstrated a direct pathway from the pontine micturition center to the dorsal gray commissure of the sacral cord in cats, 18 and suggested that the pathway relaxed the external striated sphincter during micturition via inhibitory modulation through GABA neurons in Onuf's nucleus. Furthermore, Kanie et al, 16 who performed many experiments on the mechanisms underlying bladder overactivity in CI rats, suggested that the impairment of the inhibitory GABAergic pathway that originates in the forebrain Neurourology and Urodynamics DOI 10.1002/nau Fig. 4.…”
Section: Discussionmentioning
confidence: 99%